The origins of Achilles image’s devotion by Scythians of the Northern black sea region - Лазаренко, Владимир (Дриновський збірник, 2020)
The ancient origins of Achilles image popularity of Scythian aristocracy have been examined. Several scenes from the life of Achilles, depicted on the gold plates of gorites and the gold plates of sword scabbards found in six Scythian mounds near Bosporus, are considered. We studied ancient evidence of the connection of Achilles with the Scythians and the Northern black sea region. The necessity of studying the origins of the Achilles image popularity among the Scythians in the Indo-European context is shown. This is because precisely in the Northern black sea region the main events of the formation and collapse of the Indo-European language community took place. Here, from the 4 to 1 Millennium BC, the cult of snakes was continuously spread. This took place consistently in the Trypillya culture, the Catacomb, the Srubnaya, and the Belozersk cultures. Based on this cult in this region the cult of Áhi the Snake, the Supreme deity and the first Ancestor of the early Indo-Europeans (Aryans), was formed. It then served as the Foundation for the Greek Genesis of the image of Pra-Achilles including the formation of his name. It is suggested that Achilles represented in the barbarian environment the relic Aryans (Dandariis, Tauris, Achaeans, Sinds, Maeotians) and among the Scythians of the ancient Northern black sea region the incarnation of Ahi the Serpent – the first Ancestor and Supreme God. This explains the features of Achilles cult in the Northern black sea region compared to the rest of Greece including its close connection with snakes. These representations also served as the basis for significant popularity among barbarians of stories related to Achilles and reflected, in particular, on the products of the Scythian toreutics.